Antioxidant and Cardiac Enzyme Marker Studies of Thevetia peruviana Seed Hydro-Methanol Extract in Wistar Male Albino Rats (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Thevetia peruviana seed kernels are used for suicide attempts in many countries centuries back. The aim of the present study was to evaluate the level of toxicity exposure of seed kernels by acute and subacute studies on male wistar rats taking antioxidant enzyme levels in the vital organs like liver, kidney, heart and brain tissues myocardial marker enzyme levels in serum. Results revealed that antioxidant enzyme (SOD, GPX, GSH) levels was normal in the lower groups (25, 50 mg/kg), but drastic hike was observed in CKMB and LDH cardiac biomarker enzyme levels in 100 mg/ kg groups. In the liver tissues of group IV animals a significant dose dependent increase was observed in the activities of SOD (3.15 ± 0.58), GPx (46.55 ± 4.79) and GSH activity (18.20 ± 0.56). In kidney homogenates SOD and GSH level showed a statistically insignificant (p > 0.05) elevation, but the increase in GPx level shown by group IV animals (41.50 ± 7.04) was significant (p < 0.05) The activities of SOD in brain homogenates were increased significantly in group III (2.17 ± 0.24) and group IV (2.51 ± 0.27) animals. The GPx enzyme level also increased dose dependently (p < 0.01), but the level of GSH was found an insignificant hike. The heart, supposed to be the most adversely affected organ on cardiac glycoside administration, showed undisturbed values of enzyme levels. A noticeable elevation was observed in the serum CKMB and LDH enzyme levels in a dose dependent manner, but the extract did affect only the higher dosed animals (100 mg/kg) significantly (p < 0.05), In contrary to that, tissue homogenates of subacute animals under study showed a markedly significant hike in both CKMB and LDH levels. In conclusion, the level of toxicity and safety margin is very narrow, and the seeds really take lives of organisms, whose intake is accidentally or deliberately.